Productivity, nutrient balance, and economics of monsoon rice under different nutrient management practices in two agro-ecological zones of Bangladesh - Jahan M.A.H.S.; Hossain Akbar; Timsina Jagadish; Sarkar M.A.R.; Salim M.; Farooq M.; Das Shilpi; Chaki A.K.; Hossain M.M. (Open Agriculture, 2019)
Inherently poor soil fertility and non-adoption of fertilizer recommendations based on soil test and yield targets by farmers limit the productivity and profitability from monsoon rice in Bangladesh and much of South Asia. In the Level Barind Tract (LBT; AEZ-25) and the High Ganges River Floodplain (HGR; AEZ-11) agro-ecological zones (AEZs) of Bangladesh, monsoon (aman/kharif) season transplanted rainfed rice (known as T. aman rice) is grown in large areas after maize, wheat and/or mungbeans, with residues of each crop removed from the field after grain harvest. This results in lower grain yield and lower profits in these AEZs as compared with other AEZs. Nutrient management, based on soil test, yield targets, or integrated use of inorganics and organics for each AEZ together with retention of crop residue, has the potential to increase rice yield, reduce production cost and increase income. With this hypothesis, this study was conducted to determine the optimum nutrient management practices for achieving higher yield, maintaining apparent soil nutrient balance, and obtaining high profits from monsoon rice. Twelve nutrient management options were evaluated, of which the first six were: (i) 80-16-44-12-2 kg ha-1 of N, P, K, S, Zn respectively for a high yield goal (T1; ‘HYG’); (ii) 56-12-32-8- 1.5 kg ha-1 respectively for a medium yield goal (T2; ‘MYG’); (iii) 65-13-32-9-2 kg ha-1 respectively plus 5 t ha-1 cowdung as integrated plant nutrient management system (T3, ‘IPNS’); (iv) 67-14-41-9-2 kg ha-1 respectively as a soil test-based fertilizer management strategy (T4; ‘STB’); (v) 40-9-11-0-0 kg ha-1 respectively as per farmers’ practice (T5; ‘FP’) and (vi) 0-0-0-0-0 kg ha-1 as a control (T6; ‘CON’). The remaining six treatments were the same as above but each also included the crop residue incorporation (CRI), i.e., (vii) T7, ‘HYG+CRI’; (viii) T8, ‘MYG+CRI’; (ix) T9, ‘IPNS+CRI’; (x) T10, ‘STB+CRI’; (xi) T11 ‘FP’+CRI’; and (xii) T12, ‘CON+CRI’. In both AEZs, STB plus CRI resulted in the highest rice yield (p≤0.05) followed by ‘STB’ and ‘IPNS+CRI’. In comparison with ‘FP’ and ‘CON’, each without CRI, balances were positive (p≤0.05) for P, S, Zn and B but were negative for N and K in ‘HYG’, ‘MYG’, ‘IPNS’ and ‘STB’ with or without CRI. In both AEZS, STB nutrient management had the highest (p≤0.05) net returns (526 & 487 US$ ha-1, respectively), highest benefit cost ratio (BCR; 3.54 & 3.36) and highest marginal benefit cost ratio (MBCR; 10.47 & 10.19). These were followed by STB+CRI’ and ‘IPNS’, while they were lowest (p≤0.05) for CON and FP. We recommend that nutrient application, based on soil test with incorporation of mungbean residue, followed by IPNS, could be the best strategies for achieving high yield, improving soil fertility and for fetching a higher profit from monsoon rice in Bangladesh and similar soils and growing environments of South Asia.